2021
DOI: 10.1002/onco.13797
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Radiotherapy Plus Camrelizumab for Locally Advanced Esophageal Squamous Cell Carcinoma

Abstract: Lessons Learned Radiotherapy plus anti–PD‐1 antibody as first‐line therapy is safe and feasible in locally advanced esophageal squamous cell carcinoma (ESCC). Tumor‐infiltrating and peripheral lymphocytes were associated with patient survival. Further studies combining chemoradiotherapy with immunotherapy in locally advanced ESCC and exploration of predictive biomarkers are warranted. Background We conducted a phase Ib study of radiotherapy plus programmed cell death protein 1 (PD‐1) monoclonal antibody camr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 25 publications
(39 reference statements)
2
79
1
Order By: Relevance
“…Subsequently, the current study turn attention to camrelizumab, a PD-1 immune checkpoint inhibitor, which blocks the binding site of PD-1 expressed on activated T lymphocytes, B cells, and natural killer cells to PD-L1 overexpressed on certain cancer cells. So far, several studies report that camrelizumab combined with chemotherapy has been used in adjuvant and second-line therapy of locally advanced ESCC and exhibits a promising antitumor efficacy [ 17 , 18 ]. However, the clinical value of neoadjuvant camrelizumab combined with chemotherapy in locally advanced ESCC is still unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the current study turn attention to camrelizumab, a PD-1 immune checkpoint inhibitor, which blocks the binding site of PD-1 expressed on activated T lymphocytes, B cells, and natural killer cells to PD-L1 overexpressed on certain cancer cells. So far, several studies report that camrelizumab combined with chemotherapy has been used in adjuvant and second-line therapy of locally advanced ESCC and exhibits a promising antitumor efficacy [ 17 , 18 ]. However, the clinical value of neoadjuvant camrelizumab combined with chemotherapy in locally advanced ESCC is still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Camrelizumab, a domestic product developed in China, is a novel IgG4-kappa anti-PD-1 inhibitor that has been used for treatment of a variety of malignancies, such as refractory classical Hodgkin’s lymphoma and gastric or gastroesophageal junction adenocarcinoma [ 15 , 16 ]. Moreover, camrelizumab has been previously witnessed for adjuvant or second-line therapy of locally advanced ESCC [ 17 , 18 ]. However, the clinical value of neoadjuvant camrelizumab plus chemotherapy in the treatment for locally advanced ESCC has not been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…RT can undergo a so-called immunogenic death inducing in situ vaccination and render the tumor microenvironment conducive to effector T-cell 4 recruitment and function to produce a synergistic anti-tumor immunity with anti-PD1 for durable disease control [ 15 ]. Early clinical trials combining RT with anti-PD1 showed clinical activity in several cancers including non-small cell lung cancer [ 16 ], malignant pigmented tumor [ 17 ], and esophageal squamous cell carcinoma [ 18 ]. A case report including 5 cases showed the impressive tumor control in patients with advanced HCC treated by the combination of RT and anti-PD1 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although radiotherapy evoked antitumor immune response, the proliferated T, B, and NK cells activated during radiotherapy were sensitive to radiation-induced cytotoxicity. Additionally, the on-treatment tumor biopsies were always collected during radiotherapy ( 5 , 26 ). As a result, poor relationship between the on-treatment tumor-infiltrating T cells and patient survival was observed in our present and previous study ( 4 ) ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the on-treatment tumor biopsies were always collected during radiotherapy ( 5 , 26 ). As a result, poor relationship between the on-treatment tumor-infiltrating T cells and patient survival was observed in our present and previous study ( 4 ) ( 26 ). Identifying the functional status might provide clues of the antitumor immune characteristics of these radiosensitive immune cells in further studies.…”
Section: Discussionmentioning
confidence: 99%